Market potential of TikTok in the context of the communication range of soccer players on social networks - Šíma, Jan (Acta Universitatis Carolinae. Kinanthropologica, 2021)
The study aims to put the social network TikTok into the context of the marketing attractiveness and potential of soccer players in terms of communication range through social networks. Soccer clubs can assess the expenses of gaining additional followers through a purchased player by an evaluation of the market efficiency of individual soccer players' followers. The study also documents positive effects ensuing from the acquisition of further followers thanks to the purchase of such a player including image, connection with fans, global reach, additional external funds through sponsorship and the sale of television rights, loyal fans and other so-called “extra-football qualities”. The study thus brings new perspectives on TikTok, as a network which has so far not been thoroughly researched, in the field of the most popular sport in the world, soccer.
Keywords: Social Media; sportovci; fotbal; Soccer; sociální média; užívání mobilních telefonů; Cell Phone Use; Communication; lidé; Humans; komunikace; Athletes